Two-dice horse race - Foster, Colin; Martin, David (Wiley, 2016)
In this article we analyse the “two-dice horse race” task often used in lower secondary school, in which two ordinary dice are thrown repeatedly and each time the sum of the scores determines which horse (numbered 1 to 12) moves forwards one space. The process is repeated until one horse crosses the finishing line a fixed number of spaces away. We examine the difficulties involved in calculating the probability of any particular horse winning the race and carry out a simulation to estimate these probabilities. We conclude that while this task might be a helpful way to introduce sample space diagrams, great care is needed in interpreting the outcome of the race. The greater probability of obtaining a total score of 7 on a single throw of two dice is only partly responsible for horse 7’s greater chance of winining, since the length of the track is also important.